Music for Wellness in rehabilitation patients: programme description and evaluation results. (May 2021) - Davies, C.; Shurdington, J.; Murray, K.; Slater, L.; Pearson, D.
Abstract: Objective: The evaluation of real-world, hospital-based, arts programmes is important for quality assurance, to increase knowledge of successful practice and awareness of effective arts-health collaborations. The objective of this study was to describe the Music for Wellness programme and evaluation at St John of God Frankston Rehabilitation Hospital, Australia. Study design: An impact evaluation and quasi-experimental pre-post study was conducted. Methods: The Music for Wellness programme for rehabilitation patients ran on a weekly basis for 18 weeks (i.e., 18 stand-alone workshops). Evaluation feedback was collected from patients and hospital staff/visitors. The primary outcome measures were pre-post workshop changes in patients' mood, measured via a 'faces' visual analogue scale; and pain, measured via a numerical rating scale. Linear mixed models and growth curve analyses were performed. Evaluation questions about mental well-being, pain reduction, musical skill attainment and the hospital environment were also asked and, a descriptive analysis was conducted. Results: Between the baseline, preworkshop and postworkshop time points, a significant increase in rehabilitation patients' mood and decrease in self-reported pain were found. Changes were consistent over time. The patients and hospital staff/visitors agreed the programme enhanced the hospital environment and music skills, resulted in positive benefits (e.g., relaxation, opportunity to socialise) and should be continued. Conclusion: This study provides valuable information about a low-cost, non-pharmacological programme that successfully enhanced the hospital environment and supported patients' well-being in a rehabilitation setting. Graphical abstract: Image 2